Letter : Spanish seamen - Reed, George
025a-0111-001 Telegraphic Address "Searoving Lamb London" Telephone no. WATerloo 5906 (four lines) National Union of Seamen Registered trade union no 1493 Approved Society Certificate no. 128 Formerly National Sailors & Firemens Union Founder The late J. HAVELOCK WILSON. C.H. C.B.E. General Secretary W.R. SPENCE C.B.E. General Treasurer J.B. WILSON Asst General Secretary G.REED St Georges Hall WESTMINSTER BRIDGE ROAD London S.E.1 Please quote in reply: Your ref. HVT/EK/984. Our ref. GR/MLA. All communications must be addressed to the General Secretary. Mr.H.V. Tewson, Trades Union Congress, April 21st 1939. Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, SPANISH SEAMEN. With further reference to our correspondence re the above and referring to your letter of the 14th instant, I reported to the Executive Council on this matter and also in regard to our decision to assist the Trades Union Congress in looking after the Spanish seamen who have become refugees through leaving Spanish ships in the United Kingdom. My Executive Council, whilst expressing the greatest possible sympathy with all concerned, stated that they had no intention of allowing Spanish seamen to be drafted into British ships, as we had an unemployment problem of our own to contend with, and in addition they would be foregoing certain principles that the Union fought for and maintained many years, i.e. British seamen for British ships. With regard to the maintenance of Spanish seamen, I have been instructed to say that the Union is not prepared to allow me to continue indefinitely to deal with this matter, as they are of the opinion that this is a National question and one that should be dealt with by H.M. Government. They state there is no reason why Spanish refugee seamen should not be treated in the same manner as thousands of Spanish refugees are being dealt with by the French Government in France. I would be glad, therefore, to have your views on the matters indicated above and would be prepared to assist in any approach that the Trades Union Congress desire to make to the Government in regard to this problem. As you are aware we have been paying the accounts for board and lodging in respect of these Spanish ratings from our General Fund, and I hope at the end of this month to render you a final account after completing the payments for the week ending 29th April as agreed. After that date my instructions are to hand the matter over to the Trades Union Congress for their disposal. Yours faithfully, Geo. Reed Assistant General Secretary. 292/946/25a/111